2003
DOI: 10.1183/09031936.03.00081702
|View full text |Cite
|
Sign up to set email alerts
|

Decreased computed tomographic lung density during exacerbation of asthma

Abstract: Recently, it was shown that both mean lung density (MLD) and the relative lung area with an attenuation of v-950 HU (RA950) are related to severity of asthma in nonsmoking asthmatics. The aim of the present study was to examine whether reduced computed tomography (CT) lung density during exacerbation could change after treatment.A cross-sectional study was performed to compare CT lung density in 30 stable asthmatics, 30 unstable asthmatics and 25 control subjects. In order to investigate longitudinally the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 31 publications
4
25
1
Order By: Relevance
“…In another study, the percentage of lung field occupied by low attenuation area at inspiration showed some correlation with FEV1/FVC, suggesting an association between asthma severity and small airways [60]. Furthermore, MITSUNOBU et al [61] reported decreased CT lung density during asthma exacerbations. These findings were at least partially reversible, and changes in mean lung density and the relative lung area with low attenuation were related to the change in FEV1 and RV [61].…”
Section: Imaging Techniques In the Evaluation Of Small Airways In Obsmentioning
confidence: 92%
See 1 more Smart Citation
“…In another study, the percentage of lung field occupied by low attenuation area at inspiration showed some correlation with FEV1/FVC, suggesting an association between asthma severity and small airways [60]. Furthermore, MITSUNOBU et al [61] reported decreased CT lung density during asthma exacerbations. These findings were at least partially reversible, and changes in mean lung density and the relative lung area with low attenuation were related to the change in FEV1 and RV [61].…”
Section: Imaging Techniques In the Evaluation Of Small Airways In Obsmentioning
confidence: 92%
“…Furthermore, MITSUNOBU et al [61] reported decreased CT lung density during asthma exacerbations. These findings were at least partially reversible, and changes in mean lung density and the relative lung area with low attenuation were related to the change in FEV1 and RV [61]. TUNON-DE-LARA et al [62] have shown that 3-month treatment with inhaled corticosteroids (ICS) resulted in decreased lung attenuation and air trapping.…”
Section: Imaging Techniques In the Evaluation Of Small Airways In Obsmentioning
confidence: 98%
“…airway narrowing in disease causes variation in the regional lung volume at which airways close, and this, in turn, leads to heterogeneity in lung density on scans taken at end expiration [29][30][31][32][33][34]. A limitation of the use of expiratory CT scans is the difficulty in breath-holding at low lung volume.…”
Section: Computed Tomographic Imaging Of the Airways Pa De Jong Et Almentioning
confidence: 99%
“…MITSUNOBU et al [32] showed that mean lung density on inspiratory scans decreased during exacerbations of asthma. GOLDIN et al [75] showed that the distributions of attenuation values are shifted to the left (low density) during airway narrowing in CT scans acquired before and after methacholine challenge.…”
Section: Gas Trappingmentioning
confidence: 99%
“…In nonsmokers with severe or unstable asthma, however, low-attenuation areas at TLC have also been observed in a diffuse pattern ( Figure 1C). This pattern has been attributed in various publications to hyperinflation, airflow limitation, and complexity of terminal airspace geometry (6,(12)(13)(14)(15)(16)(17) and remains comparatively understudied in asthma relative to the more common air trapping measure at FRC.…”
mentioning
confidence: 99%